When fixing problems kills personal development: fMRI reveals conflict between Real and Ideal selves - Jack, Anthony Ian; Passarelli, Angela M.; Boyatzis, Richard Eleftherios (Frontiers in Human Neuroscience, 2023)
Many coaching approaches aim to change behavior by increasing self-knowledge. However, selfknowledge can be difficult to achieve. One hypothesis (e.g. Jung, Rogers) is that self-knowledge is challenging because there is inherent conflict between different aspects of the self. This hypothesis is foundational to Boyatzis' Intentional Change Theory (ICT). ICT holds that effective coaching requires deliberate sequencing of the client's exploration of different aspects of their self. Coaches initially encourage clients to focus exclusively on their Ideal self. The ICT approach differs from that advocated by most coaching organizations that suggest collaborative goal setting at the start of the coaching engagement, encouraging clients to focus on fixing performance deficits and problematic behaviorsaspects of the Real self. If there is conflict between thinking about Ideal and Real selves, then this strategy will be suboptimal. The hypothesis of attentional conflict therefore has significant implications for coaching practice. Previous findings establish a link between attention to Ideal vs. Real selves and global vs. local visual processing, respectively. This association alone does not imply conflict because, in naturalistic settings, global and local perceptual processes usually work in concert. However, certain stimuli such as Navon figures (letters made from many smaller letters, e.g. a large E made of small R's) create conflict due to incongruence between the global and local features. Does thinking about the self inherently generate conflict, like a Navon figure, or is it more akin to everyday perception? To answer this question the current study uses functional magnetic resonance imaging to examine the overlap in brain activity in young adults between two pairs of otherwise very dissimilar tasks: coaching interactions focused on Ideal vs. Real self; and attention to global vs. local features of Navon figures. Despite the ostensible absence of overlap in the psychological processes involved in these pairs of tasks, we find a remarkable degree of overlap in brain activity. This overlap was pronounced in higher (parietal and temporal) areas known to be involved in resolving attentional conflict. These findings provide compelling biological evidence for inherent conflict between thinking about Ideal and Real selves.